Development of rabbit industry in Egypt - Galal E.S.E.; Khalil M.H. (Rabbit production in hot climates, 1994)
An estimate of 88-90 per cent of rabbit population in Egypt is in the hands of small-holders while the rest belongs to the commercial sector. Rabbits are mainly bred by families as backyard farming where small breeding units are conveniently set up not only in the villages, but also in towns. The most widespread rabbit raising system in Egypt is the one which utilizes hutches or cages. Underground cells are also used. Ten years ago, commercial rabbit farms have started to expand in Egypt and several farms are now engaged in large-scale production. Rabbits in Egypt currently fall far short from reaching the limits of their potential for carcass production. In comparison with other types of meat, the annual consumption of rabbit meat per head of population is very low (0.7 kg in 1992). Most of the local breeds of rabbits appear to be in real danger of extinction. Origin and distribution of local germplasms along with their performances were reviewed. Local breeds of rabbits (e.g., Giza White, Baladi Red, Baladi White and Baladi Black) showed, in general, lower performance than acclimatized exotic breeds (e.g., Bouscat, Chinchilla, White Giant Flander, Grey Giant Flander) for different productive traits. The genetic potentials of introduced breeds (e.g., New Zealand White and Californian) and the importance of genetic-by-environment interactions are not fully exploited under Egyptian conditions. Crossbreeding experiments including New Zealand White and Californian along with local Egyptian breeds gave evidence to the possibility of the improvement of most economic traits in rabbits in Egypt.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)